Mesenchymal stromal cells induce epithelial‐to‐mesenchymal transition in human colorectal cancer cells through the expression of surface‐bound TGF‐β. Issue 11 (30th January 2014) - Mele, Valentina; Muraro, Manuele G.; Calabrese, Diego; Pfaff, Dennis; Amatruda, Nunzia; Amicarella, Francesca; Kvinlaug, Brynn; Bocelli‐Tyndall, Chiara; Martin, Ivan; Resink, Therese J.; Heberer, Michael; Oertli, Daniel; et al.
<x xml:space="preserve">Abstract</x> Mesenchymal stem/stromal cells (MSC) are multipotent precursors endowed with the ability to home to primary and metastatic tumor sites, where they can integrate into the tumor‐associated stroma. However, molecular mechanisms and outcome of their interaction with cancer cells have not been fully clarified. In this study, we investigated the effects mediated by bone marrow‐derived MSC on human colorectal cancer (CRC) cells in vitro and in vivo. We found that MSC triggered epithelial‐to‐mesenchymal transition (EMT) in tumor cells in vitro, as indicated by upregulation of EMT‐related genes, downregulation of E‐cadherin and acquisition of mesenchymal morphology. These effects required cell‐to‐cell contact and were mediated by surface‐bound TGF‐β newly expressed on MSC upon coculture with tumor cells. In vivo tumor masses formed by MSC‐conditioned CRC cells were larger and characterized by higher vessel density, decreased E‐cadherin expression and increased expression of mesenchymal markers. Furthermore, MSC‐conditioned tumor cells displayed increased invasiveness in vitro and enhanced capacity to invade peripheral tissues in vivo. Thus, by promoting EMT‐related phenomena, MSC appear to favor the acquisition of an aggressive phenotype by CRC cells.